1998
DOI: 10.1111/j.1471-0528.1998.tb10211.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in long term users of depot medroxyprogesterone acetate

Abstract: Objective To identify any adverse effect on bone density in long term users of depot Design Cross-sectional measurement of bone density in users with amenorrhoea of more than one Setting Community Family Planning Clinics in Portsmouth and Manchester.Population One hundred and eighty-five women aged 17-52 years (mean 33.3 years) who had used DMPA for between 1 and 16 years and were attending the clinics for further injections, between August 1994 and August 1996. Methods Dual energy X-ray measurement of bone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(22 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…Two studies have failed to show a correlation between serum oestradiol levels and BMD. 102,103 The CEU suggests that women aged over 40 years who are continuing or considering initiation of DMPA should be advised that studies have found an association between long-term use and loss of BMD. Women with additional risk factors for low BMD (i.e.…”
Section: The Relationship Between Bone Densitometry and Fracture Riskmentioning
confidence: 99%
“…Two studies have failed to show a correlation between serum oestradiol levels and BMD. 102,103 The CEU suggests that women aged over 40 years who are continuing or considering initiation of DMPA should be advised that studies have found an association between long-term use and loss of BMD. Women with additional risk factors for low BMD (i.e.…”
Section: The Relationship Between Bone Densitometry and Fracture Riskmentioning
confidence: 99%
“…A FACT 2 on Depo-Provera and bone density mentions that cross-sectional studies have shown that serum oestradiol levels in users may range from 15 to 318 pmol/l, [3][4][5][6] and that after up to 5 years of use most women have serum oestradiol levels above those of postmenopausal women. Additionally, these serum oestradiol levels are found to be in the early follicular phase range for women who ovulate.…”
Section: Evidence Reviewed Existing Ffprhc and Royal College Of Obstementioning
confidence: 99%
“…In addition, the FACT mentions two studies that have shown that there is no significant correlation between bone density and serum oestradiol levels. 5,6 The recommendations made by the FACT are: l All women who are considering the use of DMPA should be told that studies have found an association between long-term DMPA use and loss of bone mass. l Women should be encouraged to build up, or maintain, their bone mass through attention to diet and exercise while those with risk factors for low BMD, such as smokers or those on long-term high-dose corticosteroid therapy, should be discouraged from using this contraceptive method.…”
Section: Evidence Reviewed Existing Ffprhc and Royal College Of Obstementioning
confidence: 99%
“…However, there are no published studies showing a linear relationship between oestradiol levels and BMD in these patients; in fact, two studies showed that there was no significant correlation between bone density and serum oestradiol level. 6,7 Several studies have sought to ascertain the effects of long-term use of Depo-Provera ® on bone density but the results have been mixed. This is not surprising given the fact that most of the studies have been cross-sectional in design, of short duration, and have used different measuring techniques at different sites in different population groups with small numbers.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…4 Cross-sectional studies show that serum oestradiol levels range from 15 to 318 pmol/l. 3,[5][6][7] In nearly all women, after up to 5 years of Depo-Provera ® use, serum oestradiol levels remain above those found in postmenopausal women. Serum levels of oestradiol are maintained in the range found in the early follicular phase of women with ovulatory cycles.…”
Section: Mechanism Of Actionmentioning
confidence: 99%